Evaluating the practices of student teachers in teaching mathematics in resource rooms in Jordan - Beirat, Mohammad Ahmed; Almakanin, Hisham AbdAlfattah; Alkhamaiseh, Zaidan (Journal of Educational and Psychological Sciences, 2025)
The study aimed to determine the extent to which pre-service teachers practice mathematics instruction in learning disabilities resource rooms, as perceived by learning disabilities teachers in Jordan. To achieve the study’s objective, the researchers employed the descriptive survey method using a questionnaire. The researchers developed an instrument to measure mathematics teaching practices, consisting of 40 items distributed across four domains: instructional planning, classroom management and organization, instructional implementation, and instructional assessment. The instrument was administered to a sample of 75 male and female teachers working with students with learning disabilities in resource rooms in the governorates of Amman and Zarqa. The results indicated that the level of mathematics teaching practices by pre-service teachers, from the perspective of learning disabilities teachers, was moderate. The results also revealed statistically significant differences in the level of mathematics teaching practices attributed to the university GPA variable. These differences favored pre-service teachers with a “Good” GPA compared to those with a “Very Good” GPA, except in the domain of classroom management and organization, where the differences favored pre-service teachers with an “Excellent” GPA. Meanwhile, the results showed no statistically significant differences in the level of teaching practices attributed to the variables of gender, number of completed credit hours in the bachelor’s program, or the field training institution.